A new method for calculating hot-spot stress in gap DKK CHS joints under arbitrary loading. (1st May 2020) - Oshogbunu, Ernest O.; Wang, Yong C.; Stallard, Tim
Highlights: New stress concentration factor equations for gap double K joints under arbitrary brace loading condition. Complete stress concentration factor distributions around weld toe of all brace members. Greatly improved accuracy compared to existing methods. Confirmation against extensive simulation results using validated ABAQUS model. Abstract: This paper presents a new method to calculate stress concentration factors (SCF) and hot-spot stresses in gap double K (DKK) circular hollow section (CHS) joints used in construction of offshore wind turbine jacket support structures. The focus of this paper is to overcome important limitations of existing analytical methods due to their unsuitability for application under arbitrary loading and their inability to account for carryover stresses. The proposed new analytical method consists of two steps: in the first step, an arbitrary brace loading condition in any DKK CHS joint is decomposed into symmetric and anti-symmetric axial, in-plane bending and out-of-plane bending unit load cases. In the second step, 11 key SCFs are identified and used to calculate SCF distributions around the four weld perimeters of the brace-chord connections under the aforementioned unit load cases, including carryover SCFs. These SCF distributions can be combined to calculate stress distributions and hot-spot stresses under any arbitrary brace loading condition in the DKK joint. Based on the results of an extensive numerical parametric study, regression equations have been found for calculating the 11 key SCFs. The proposed method has been demonstrated to calculate hot-spot stresses much more accurately than the most widely current used method.